2020
DOI: 10.1039/d0ra05974a
|View full text |Cite
|
Sign up to set email alerts
|

Artificial sugar saccharin and its derivatives: role as a catalyst

Abstract: The primary objective of this review was to demonstrate the significance of artificial sugar saccharin and its derivatives as catalysts for a wide variety of organic transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 169 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Having established efficient protocols for the preparation of 2,3-diphenyl-2,3-dihydroquinazolin-4(1H)-one through the condensation reaction of isatoic anhydride with aldehydes and ammonium salts (or amines), it is observed that an unexpected product were isolated, after characterisation it was revealed that the catalyst exhibited a catalyzed cyclization and a subsequent oxidation of 2,3-dihydroquinazolin-4(1H)-ones. N-Bromosaccharin was identified as a chemoselective nitrogen radical precursor that undergoes controllable homolytic cleavage under ambient light irradiation [32] and also taking the oxidizing property of N-Bromosaccharin [25][26][27][28][29] into account, we have tried to optimize the reaction conditions for the oxidation of 2,3-dihydroquinazolin-4(1H)-ones to 2-quinazolin-4(3H)-ones (Table 2) in presence of visible light. For this, 2,3-dihydroquinazolin-4(1H)-one (4 a) was taken as model reactant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having established efficient protocols for the preparation of 2,3-diphenyl-2,3-dihydroquinazolin-4(1H)-one through the condensation reaction of isatoic anhydride with aldehydes and ammonium salts (or amines), it is observed that an unexpected product were isolated, after characterisation it was revealed that the catalyst exhibited a catalyzed cyclization and a subsequent oxidation of 2,3-dihydroquinazolin-4(1H)-ones. N-Bromosaccharin was identified as a chemoselective nitrogen radical precursor that undergoes controllable homolytic cleavage under ambient light irradiation [32] and also taking the oxidizing property of N-Bromosaccharin [25][26][27][28][29] into account, we have tried to optimize the reaction conditions for the oxidation of 2,3-dihydroquinazolin-4(1H)-ones to 2-quinazolin-4(3H)-ones (Table 2) in presence of visible light. For this, 2,3-dihydroquinazolin-4(1H)-one (4 a) was taken as model reactant.…”
Section: Resultsmentioning
confidence: 99%
“…[24] N-Bromosaccharin (NBSac) is an excellent reagent due to its characteristics such as easy preparation, low cost and non-metallic nature but it is rarely used in organic synthesis. [25] It act as a brominating agent. [26] It is also used as a catalyst for oxidative cleavage of oximes to the corresponding aldehydes and ketones, [27] chemoselective oxidation of thiols to their corresponding disulfides, [28] and synthesis of oxathiolane from aldehydes and ketones with 2-mercaptoethanol.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, intensive efforts have been made toward the synthesis of new saccharine derivatives as potential bioactive compounds [17]. In addition, the application of these derivatives in catalysis [18], polymers [19] and coordination chemistry [20] has significantly increased.…”
Section: Introductionmentioning
confidence: 99%
“…As an important additive in the food industry, the safety issue of saccharin, however, became disputable since the 1970s, concerning its potential adverse health effects. 1,2 Moreover, exposure to saccharin may disrupt intestinal epithelial cell barrier function in vitro, as evidenced by Santos. 3 As such, the Food and Drug Administration of the United States officially prohibited the addition of saccharin into food once in 1977, which was repealed later.…”
Section: Introductionmentioning
confidence: 99%